WILCOXON RANK-SUM HYPOTHESIS TESTING OF MILITARY BUDGETS AS A PERCENTAGE OF GROSS DOMESTIC PRODUCT AND GOVERNMENT SPENDING - Endro Tri Susdarwono; Alma Wiranta (Universitas Lambung Mangkurat, 2025)
This study aims to describe the policy of determining military budget size as a percentage of Gross Domestic Product (GDP) and government spending in countries in Asia, Oceania, and Africa. The approach used in this study is descriptive quantitative. The data used are national defense allocations published by SIPRI. Data analysis used a hypothesis test with a Wilcoxon rank sum. This study concluded that for hypothesis testing with a Wilcoxon rank sum and using the same sample size and no more than 20 samples, the policy of determining military budget size as a percentage of Gross Domestic Product (GDP) in Asian and African countries differs. For testing with a different sample size and no more than 20 samples, the policy of determining military budget size as a percentage of Gross Domestic Product (GDP) in Asian and African countries is the same. Based on hypothesis testing with a Wilcoxon rank sum and using a sample size greater than 20 samples, the policy of determining military budget size as a percentage of government spending in Asian, Oceania, and African countries differs.